Community transformed? Exploring the interaction between online support and rural community life for people with acute mental health conditions. (April 2023) - Kilpatrick, Sue; Farmer, Jane; Emery, Sherridan; Kamstra, Peter; Steiner, Artur; McCosker, Anthony; Carlisle, Karen
Abstract: Since the onset of COVID-19, the benefits of online platforms to enhance rural service accessibility are more acknowledged. However, questions remain about the interconnected roles of geographical community and online digital communities in enhancing rural life – particularly for marginalised groups. In this study, we examine one Australian non-profit's online peer support forums as technology enabling transformed community experiences for rural people with mental health conditions. Interviews exploring forum use were conducted with 20 rural forum users in 2021. We found technology affordances were appropriated to target rural service and social interaction gaps, giving people resources used online, and also enabling coping in their geographical community. The study illustrates the benefits of understanding what rural people do with different technologies that can illuminate how apparently "one-size-fits-all" technologies can be appropriated to fill certain rural structural holes in social and service systems. Highlights: Digital technologies can target key health service and social interaction gaps. Online mental health forums can support rural people to cope in their communities. Such technologies can be used by rural people to address gaps and problems. Online forums may be efficacious but cannot replace offline clinical treatment. Technologies should be integrated into rural health service system design processes.